Financial Literacy and Financial Behaviour of Students in the Digital Economy Era in Pontianak - Saragih, Fry Melda (Universitas Ibn Khladun Bogor, 2024)
This research investigates how financial literacy impacts the financial actions of Pontianak university students, considering factors like financial socialization, attitude, and education. Employing a quantitative, cross-sectional approach, data was gathered from 520 students via Google Forms and analyzed using PLS-SEM. The findings indicate that financial socialization and attitude significantly and positively affect both financial education and behavior. Financial education also positively influences financial behavior. However, financial literacy itself did not significantly impact financial education or behavior. The study confirms that financial education mediates the relationship between financial socialization and attitudes. Interestingly, financial literacy does not have a mediating effect. The results suggest that Pontianak universities could use this information to develop curricula emphasizing financial literacy in today's digital economy. Furthermore, it can help prepare students for future financial challenges, fostering a more financially savvy generation in the digital age and providing a basis for evaluating accounting and finance programs.